A Conceptual Examining of the Interplay Between Technical and Conceptual Skills of Social Media Managers as Predictors of Job Performance: The Moderating Influence on Brand Equity - Alateya, Abbas Alwan Ghazi; Baskaran, Shathees (Business Management and Strategy, 2024)
This study explores the impact of social media managers'(SMM) technical and conceptual skills on job performance, with brand equity as a moderating factor. As social media usage grows, firms integrate it into marketing plans, necessitating research on its influence on job performance. Expected positive outcomes include marketing performance, cost effectiveness, operational excellence, and customer satisfaction. The research aims to enhance theoretical understanding of social media managers' roles and guide organizations in leveraging their contributions to boost employee job performance. Empirical testing will further illuminate the link between technical and conceptual skills, job performance, brand equity, and social exchange theory.